DEVELOPMENT OF AGRO-FOOD TRADE BETWEEN POLAND AND GEORGIA IN TERMS OF DCFTA EU-GEORGIA (Globalization and Business, 2018)
The EU signed the Association Agreements with between Poland and Georgia. From the Polish perspective,Georgia is not a significant trading partner. However, for many Polish companies, the Georgian market may be a part of the export diversification strategy, which aims to reduce their dependence on sales to EU Member States. It seems that there are further opportunities for the development of Polish food export to Georgia. Poland imports from Georgia mainly wine, nuts and fruits, which are complementary to the domestic production. It can be expected that GIs protection may bring benefits to Georgian producers of wine, for which demand in the EU, including Poland, is systematically growing. Georgia on 27 June 2014. Substantial part of this Agreement, mincluding the DCFTA sections are provisionally applied as of 1 September 2014. The agreements with Georgia have been ratified and officially entered into force in July 2016. Under the DCFTA, the EU and Georgia removed all their import duties on agricultural products. However, it seems that more important are non-tariff barriers in mutual trade because EU and Georgia had different approaches to food safety and different regulations. The purpose of this article is to assess the impact of DCFTA UE-Georgia on the development of agri-food trade.